Secrets in the fire - Mankell, Henning, 1948-; Struksrud, Anne Connie (Australia : Allen & Unwin, 2000)
Presents a fact-based novel that explores the experiences of Sofia, a young girl from southern Africa who must struggle to rebuild her life after losing her legs in a land mine explosion.
Translated from the Swedish.
Translation of: Eldens Hemlighet.
Young Adult.
Young Adult
Keywords: Girls -- Mozambique -- Juvenile fiction; Land mines -- Juvenile fiction; Girls -- Mozambique -- Fiction; Land mines -- Fiction; Girls -- Mozambique -- Fiction; Land mines -- Fiction; Mozambique -- Juvenile fiction; Mozambique -- Fiction; Mozambique -- Fiction